Discussion on Automatic Service Open Method Based on Smart TV Terminal - Weijia Shi; Liding Jia; Liangjie Zhu (Dianxin kexue)
Based on the analysis of the evolution of smart TV terminal，the traditional way of service open by operators and the changes aroused from the appearing of smart TV terminal were introduced.According to the changes above，two alternative ways of automatic service open were presented and compared in detail in order to put forward the suggestions for the way of automatic service open.